IMPROVING THE VOCABULARY OF SPECIAL NEEDS STUDENTS THROUGH THE DRILLING METHOD AT PKBM WINDSOR BEKASI - HENNY, HENNY; EDI, SYAMSI; RUSMIATI, YANTI (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2024)
This study aims to describe the implementation of the Drilling Method at PKBM Windsor Homeschooling Bekasi, this study used the action research method. Data collection was taken by a series of steps: planning, action, observation, and reflection. Two special needs students at PKBM Windsor Bekasi served as the research objects. Research results show that the drilling method can be implemented well. Research indicates that using the drilling method can improve students' vocabulary mastery. Based on observation, the results show an increasing growth of vocabulary and understanding, an average of 70%, a significant result for special needs students, from cycles 1-6. The results of this research are important for improving special needs students' vocabulary. ABSTRAKKajian ini bertujuan untuk mendeskripsikan implementasi metode drilling yang dilaksanakan di Homeschooling PKBM Windsor Bekasi. Studi ini menggunakan metode penelitian tindakan kelas. Data diperoleh melalui perencanaan, tindakan, observasi dan refleksi. Subjek penelitian adalah dua siswa berkebutuhan khusus di PKBM Windsor Bekasi. Hasil penelitian menunjukkan bahwa metode drilling telah dilaksanakan dengan baik. Penelitian, yang menunjukkan bahwa penggunaan metode drilling dapat meningkatkan penguasaan kosakata siswa berkebutuhan khusus. Berdasarkan pengamatan, hasilnya menunjukkan peningkatan pertumbuhan dan pemahaman kosakata. rata-rata sebesar 70%, hasil yang signifikan bagi siswa perlu khusus, dari siklus 1-6. Hasil penelitian ini memberikan makna penting bagi peningkatan kebutuhan kosakata siswa khusus.